Efektivitas Model Project Based Learning (Pjbl) Terhadap Hasil Belajar Biologi Peserta Didik Kelas X SMA Negeri 4 Pinrang Materi Perubahan Lingkungan dan Upaya Mengatasinya - Kamaruddin, Fatmah; Pagarra, Halifah; Nurhayati B, Nurhayati B (Universitas Negeri Makassar, 2020)
Abstract.Â This study aims to determine the effect of the Project Based Learning model on student learning outcomes onÂ environmental change material for class X SMA Negeri 4 Pinrang. This type of research is quasi-experimental research (Quasy Experimental). The sample of this study were students of class X MIA SMA Negeri 4 Pinrang who were selected by random sampling. In class X MIA 3 as an experimental class that is given treatment by learning using the PjBL learning model, while in class XI MIA II as a control class is taught using a direct learning model. The data collection technique used is in the form of multiple choice (multiple choice) as many as 25 items. The collected data were analyzed using descriptive statistics and inferential statistics. The results showed that students who were taught with the Project Based Learning (PjBL) learning model had an average score of 73.0 in the very good category. Meanwhile, the learning outcomes of students who were taught with the direct learning model had an average score of 71.29 in the good category and there was an influence of the Project Based Learning (PjBL) learning model on student learning outcomes on environmental change material at SMA Negeri 4 Pinrang.Keyword:Â learning models, Project Based Learning (PjBL), learning outcome